2013
DOI: 10.1371/journal.pone.0063612
|View full text |Cite
|
Sign up to set email alerts
|

Early versus Late-Phase Consolidation of Opiate Reward Memories Requires Distinct Molecular and Temporal Mechanisms in the Amygdala-Prefrontal Cortical Pathway

Abstract: The consolidation of newly acquired memories involves the temporal transition from a recent, less stable trace to a more permanent consolidated form. Opiates possess potent rewarding effects and produce powerful associative memories. The activation of these memories is associated with opiate abuse relapse phenomena and the persistence of compulsive opiate dependence. However, the neuronal, molecular and temporal mechanisms by which associative opiate reward memories are consolidated are not currently understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
4
17
0
Order By: Relevance
“…They also agree with those showing that the hippocampus is required early and late after training for memory processing of single trial aversively-motivated tasks (Katche, Cammarota, & Medina, 2013). Interestingly, consolidation of an opiate-reward memory also required differential molecular pathways at early and late post-conditioning phases in the amygdala and medial prefrontal cortex respectively (Gholizadeh et al, 2013). While these results suggests that dopamine in the hippocampus via activation of D1-like receptors is important for the acquisition of a non-persistent single-pairing cocaine CPP memory, recently results obtained when studying the persistence of appetitive memories showed that dopamine has a deleterious effect in maintaining the storage of multi-trial cocaine CPP memory via activation of D5 receptors (Kramar et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…They also agree with those showing that the hippocampus is required early and late after training for memory processing of single trial aversively-motivated tasks (Katche, Cammarota, & Medina, 2013). Interestingly, consolidation of an opiate-reward memory also required differential molecular pathways at early and late post-conditioning phases in the amygdala and medial prefrontal cortex respectively (Gholizadeh et al, 2013). While these results suggests that dopamine in the hippocampus via activation of D1-like receptors is important for the acquisition of a non-persistent single-pairing cocaine CPP memory, recently results obtained when studying the persistence of appetitive memories showed that dopamine has a deleterious effect in maintaining the storage of multi-trial cocaine CPP memory via activation of D5 receptors (Kramar et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Intra-BLA pharmacological blockade of CaMKII, however, blocks morphine-and heroin CPP-establishment [102,105]. This effect is most evident in the late phase of CPP consolidation 12h post conditioning [106]. CaMKIV is required for the establishment of morphine-induced CPP in mice, since CaMKIV KO mice show a significantly reduced CPP for morphine [107].…”
Section: Cppmentioning
confidence: 96%
“…This could then lead to increased drug seeking and taking (Goodman and Packard, 2016;Rosen et al, 2015). At present, few studies have directly explored the neurocircuitry underlying consolidation of drug memories (Gholizadeh et al, 2013;Hsu et al, 2002;Rosen et al, 2015;Tzschentke, 2007). Some evidence has implicated the hippocampal-cortical (Anagnostaras et al, 2001;Maren, 2001) and basolateral amygdala-PFC circuits identified in the consolidation of emotional (fear) memories (Frankland, 2004;Nader, 2015) in consolidation of drug-induced CPP (Rosen et al, 2015;Sun et al, 2011;Tzschentke, 2007).…”
Section: Neurocircuitrymentioning
confidence: 99%
“…Some evidence has implicated the hippocampal-cortical (Anagnostaras et al, 2001;Maren, 2001) and basolateral amygdala-PFC circuits identified in the consolidation of emotional (fear) memories (Frankland, 2004;Nader, 2015) in consolidation of drug-induced CPP (Rosen et al, 2015;Sun et al, 2011;Tzschentke, 2007). Gholizadeh et al (2013) used protein synthesis inhibition to show that early consolidation (0-6 h) of morphine-induced CPP requires the basolateral amygdala, while late consolidation (6-12 h) requires the PFC (Gholizadeh et al, 2013). The majority of research has instead focused on identifying the neurocircuitry-mediating acquisition and expression of drug memories.…”
Section: Neurocircuitrymentioning
confidence: 99%